Adhesive Interactions between Mononuclear Phagocytes and Intestinal Epithelium Perturb Normal Epithelial Differentiation and Serve as a Therapeutic Target in Inflammatory Bowel Disease. (16th June 2018) - Ihara, Sozaburo; Hirata, Yoshihiro; Hikiba, Yohko; Yamashita, Aya; Tsuboi, Mayo; Hata, Masahiro; Konishi, Mitsuru; Suzuki, Nobumi; Sakitani, Kosuke; Kinoshita, Hiroto; Hayakawa, Yoku; Nakagawa, Hayato; et al.
Abstract: Background and Aims: Disturbance of intestinal homeostasis is associated with the development of inflammatory bowel disease [IBD], and TGF-β signalling impairment in mononuclear phagocytes [MPs] causes murine colitis with goblet cell depletion. Here, we examined an organoid–MP co-culture system to study the role of MPs in intestinal epithelial differentiation and homeostasis. Methods: Intestinal organoids were co-cultured with lamina propria leukocytes and bone marrow–derived dendritic cells [BMDCs] from CD11c-cre Tgfbr2 fl/fl mice. Organoid–MP adhesive interactions were evaluated by microscopy, RT-PCR, and flow cytometry. Murine colitis models (dextran sodium sulphate [DSS], CD11c-cre Tgfbr2 fl/fl, T-cell-transfer) were used for histological and immunohistochemical analysis. Anti-E-cadherin antibody treatment or CD11c + -cell-specific CDH1 gene deletion were performed for E-cadherin neutralization or knockout. Colonic biopsies from patients with ulcerative colitis were analysed by flow cytometry. Results: Intestinal organoids co-cultured with CD11c + lamina propria leukocytes or BMDCs from CD11c-cre Tgfbr2 fl/fl mice showed morphological changes and goblet cell depletion with Notch signal activation, analogous to CD11c-cre Tgfbr2 fl/fl colitis. E-cadherin was upregulated in CD11c + MPs, especially CX3 CR1 + CCR2 + monocytes, of CD11c-cre Tgfbr2 fl/fl mice. E-cadherin–mediated BMDC adhesion promoted Notch activation and cystic changes in organoids. Anti-E-cadherin antibody treatment attenuated colitis in CD11c-cre Tgfbr2 fl/fl and T-cell–transferred mice. In addition, E-cadherin deletion in CD11c + cells attenuated colitis in both CD11c-cre Tgfbr2 fl/fl and DSS-treated mice. In patients with ulcerative colitis, E-cadherin expressed by intestinal CD11c + leukocytes was enhanced compared with that in healthy controls. Conclusions: E-cadherin–mediated MP–epithelium adhesion is associated with the development of colitis, and blocking these adhesions may have therapeutic potential for IBD.